The Importance of Posterior Tibial Slope Correction in the Repair of Posterior Cruciate Ligament Injuries - Lança, Pedro; Rodeia, Joaquim; Alçada, Rita; Silva, Nuno; Figueiredo, Miguel Pádua (Brazilian Journal of Case Reports, 2026)
The posterior cruciate ligament (PCL) is the primary structure responsible for limiting posterior translation of the tibia relative to the femur. PCL injuries are associated with anteroposterior instability of the knee joint. In the management of these injuries, increasing emphasis has been placed on correcting coronal (varus or valgus) and sagittal (posterior tibial slope [PTS]) plane deformities. We present the case of an approximately 50-year-old patient with right-sided knee pain localized to the medial compartment, associated with complaints of posterior instability. Imaging studies demonstrated medial chondropathy in a varus knee with a chronic PCL injury. The patient underwent a medial opening-wedge tibial osteotomy combined with an increase in the posterior tibial slope. Postoperatively, the patient showed favorable clinical improvement, with resolution of pain and no residual complaints of sagittal instability. Radiographic evaluation confirmed adequate correction of both coronal and sagittal alignment. This case demonstrates the impact that biplanar periarticular knee osteotomy can have on improving the clinical outcomes of patients with chronic PCL injuries.